Los debates y las propuestas políticas del Partido Socialista de Argentina, entre la crisis mundial y el peronismo, 1930-1950 - Graciano, Osvaldo (Revista Complutense de Historia de América, 2008)
The objective of this work is to analyze how between the world-wide crisis of 1929 and the second postwar period, the Socialist Party of Argentina was revealed as a singular theoretical and political space of debate, able to produce a systematic diagnosis of the crisis of the liberal capitalism and the parliamentary democracies and to put in revision its ideological positions and political strategies. They are reconstructed with this aim, as much as the discussions that opposed to the Great Depression were originated in the socialism and that took it to design an economic program that gave answers to argentine capitalism like the positions that defended their adoption of revolutionary and marxist tactics, revitalized by the suppression of the democratic system, thus defining alternative ways for their political action.